Rancang Sistem Informasi Sinkron Untuk Memperluas Pemasaran Dan Mengelola Transaksi: Design A Syncron Information System to Expand Marketing and Manage Transactions - Ammara Diani Yusuf; M.Fahrul Muchlis; M. Ardiansyah; Nadia Alya Putri; Zeldi Firman (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2024)
The importance of information systems has significantly increased in today's era of globalization, becoming a crucial prerequisite and success factor for both private and public organizations. This study aims to design a web-based information system for "Sinkron," a digital printing business located in Pekanbaru. Utilizing the Sequential Linear method, this research has developed an information system that enhances marketing reach and effectively manages transactions. The programming languages used include HTML, CSS, PHP, and MySQL. This information system assists business owners in promoting and marketing their products, facilitating transactions from product viewing, ordering, and payment, to providing online sales reports. Additionally, the system enables the expansion of new markets previously constrained by time, distance, and communication limitations, while reducing promotion costs by leveraging social media. This system is expected to improve the operational efficiency and competitive edge of the "Sinkron" business.